The Impact Of Glare During Daylight on Driving Performance: An Experimental Setup - Mohd Najib, Suhaila; Ab Wahab, Norfariza; Hassan, Muhammad Zahir; M.A. Che Roselam; M. H. Johari; A. H. Ariffin (Society of Automotive Engineers Malaysia, 2021)
An Advanced Rear Visualization (ARV) based on camera technology is becoming more widely available in the automobile market as it increases the ability to see beyond the area of a mirror's image as well as helping to eliminate the driver’s blind spot. Besides, it assists the driver in parking, reversing, and maneuvering safely. Therefore, it is necessary to understand how people use them to do so effectively and efficiently. This paper describes an experimental setup to observe the driver’s behavior while reverse parking the car with and without the use of a camera as well as to observe the impact of glare during daylight on the driving performance. An area of 14 meters x 12 meters is designed as the Test Environment (TE) to fit in two parking spaces. Three cameras are used to monitor the participant’s head movements and eye movements. This research is designed to study and collect driver behavior data including the reaction time taken during parking concerning the driver with different age groups, camera usage during a sunny day, and also two different parking conditions which are parallel parking and perpendicular parking. This setup is expected to be implemented to forecast the camera usage among the drivers to help the driver park their car in the reverse direction to solve the limited blind spot issue. Collected data from this study will be used as the preliminary data for road test evaluation. It is to further study the impact of glare during daylight on driving performance.